Implementasi Teologi Antroposentris Hassan Hanafi dalam Pengelolaan Sumber Daya Alam bagi Kesejahteraan Masyarakat - Subekti, Fiqi Restu (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
There are still many instances of natural resource management that fail to provide benefits and, in fact, often harm the community. The potential of Indonesia's natural resources, which should be utilized for the prosperity and welfare of the people, remains far from that expectation. Therefore, this research aims to propose the concept of Hassan Hanafi's anthropocentric theology to be implemented in managing and utilizing natural resources to improve community welfare. This study employs a qualitative method with a literature review approach. This research indicates that Hassan Hanafi's anthropocentric theology is relevant to natural resource management. Through the attribute of wujud, there is an awareness of the abundant potential of natural resources. Through the attribute of qidam, past mistakes regarding environmental destruction due to excessive resource exploitation are highlighted. Through the attribute of baqa, there is an awareness of the need to preserve and care for nature to ensure sustainability for future use. Through the attribute of mukhalafah lil hawadits, individuals are encouraged to be creative and innovative in utilizing natural resources. The attribute of qiyamuhu bi nafsih fosters independence without external intervention. Lastly, through the attribute of wahdaniyah, there is an awareness of the importance of unity and synergy in managing natural resources.